Systemic Levamisole-Induced Vasculitis in a Cocaine User without Cutaneous Findings: A Consideration in Diagnosis - Gillian G. Baptiste; Anastasia-Stefania Alexopoulos; Tahsin Masud; Joanna M. Bonsall (Case Reports in Medicine)
Levamisole is a known immunomodulating agent frequently used as a cutting agent in cocaine consumed in the United States today. Numerous cases of anti-neutrophil cytoplasmic antibody (ANCA) vasculitis connected with the use of levamisole-adulterated cocaine have previously been reported in the literature, classically characterized by a retiform purpuric rash. We report a case of a crack-cocaine user without cutaneous abnormalities who developed ANCA-associated glomerulonephritis that progressed to renal failure. This case demonstrates the difficulties in solidifying the diagnosis of levamisole-induced vasculitis in the absence of cutaneous findings and the need to pursue more testing to establish causality in ANCA-associated vasculitis that has potential for severe end-organ damage in patients who continue to use cocaine.